Safety of oral JAK inhibitors in treating alopecia areata: a systematic review and network meta-analysis - Qi, Ziyu; Li, Yan (Frontiers in Pharmacology, 2025)
ObjectiveTo assess the safety profile of oral Janus kinase (JAK) inhibitors for treating alopecia areata (AA) among adults.MethodsA comprehensive search was conducted up to July 2025 across PubMed, Cochrane Library, Embase, and Web of Science for randomized controlled trials (RCTs) on oral JAK inhibitors in managing AA. Two qualified investigators conducted a separate review of the studies, evaluated their quality, and gathered pertinent information. R was utilized for all statistical evaluations, while the “GeMTC” package facilitated the Bayesian network meta-analysis.ResultsIn this analysis, 12 studies encompassing 3,840 individuals were examined. The findings from the network meta-analysis suggested that oral JAK inhibitors were generally safe for managing AA. Nonetheless, Baricitinib was linked to an increased likelihood of developing acne (RR [95% CrI] = 4.66 [2.00, 13.44]), urinary tract infections (RR [95% CrI] = 2.72 [1.14, 8.44]), and hyperlipidemia (RR [95% CrI] = 1.77 [1.44, 2.20]). Deuruxolitinib was tied to an increased probability of acne occurrence (RR [95% CrI] = 2.74 [1.58, 5.29]) and elevated creatine phosphokinase (CPK) levels (RR [95% CrI] = 1.98 [1.11, 3.93]). Similarly, ritlecitinib was connected to a greater likelihood of elevated CPK levels (RR [95% CrI] = 2.31 [1.01, 6.70]). The experimental data, which included different dose groups, were further analyzed through subgroup analysis. The results indicated that Baricitinib and Deuruxolitinib exhibited dose-dependent differences in the occurrence of acne and elevated CPK levels.ConclusionOral JAK inhibitors exhibit a favorable safety profile for the treatment of AA. However, baricitinib is more likely to cause acne and infections as opposed to other agents.